CXCL14 is a natural inhibitor of the CXCL12–CXCR4 signaling axis. Issue 12 (11th May 2013) - Tanegashima, Kosuke; Suzuki, Kenji; Nakayama, Yuki; Tsuji, Kohei; Shigenaga, Akira; Otaka, Akira; Hara, Takahiko
Abstract : CXCR4 physically interacts with CXCL14 anti bait coimmunoprecipitation by (View interaction). Abstract : CXCL14 binds to CXCR4 with high affinity. CXCR4 is a major binding component of the CXCL14 receptor. CXCL14 inhibits the CXCL12‐mediated chemotaxis of immune cells.